AESTHETIC VALUES SUFISM IN FORMING OF THE SOLIDARITY IN URBAN COMMUNITY - Ichmi Yuni Arinda Rohmah (Populis : Jurnal Sosial dan Humaniora, 2019)
Abstract Sufisme have long been rooted in some groups of Indonesian society. One thing that is unique to the Sufi community in metropolitan cities in Indonesia is that its adherents are not only Muslims but also non-Muslims. Research conducted by the researcher intends to examine the existence of Sufism in the urban community environment, the researcher also examines the aesthetic values of Sufism which are the attraction of urban society to follow Sufi teachings, and researchers conduct research on the solidarity of the community formed in urban communities in Indonesia . The location of this research is in the capital city of Indonesia, Jakarta. This study uses a type of phenomenological (qualitative) research method. Extracting field data using interview, observation, and documentation techniques. The results of the study explain that the teachings of Sufism still exist in urban communities that are in the midst of the life of the metropolitan city of Jakarta, Indonesia. The Sufism community that teaches Sufi teachings can be accepted by most urban communities. One of the driving factors that makes urban society to study the teachings of Sufism is the aesthetic value of Sufism, besides that the Sufism teachings are built in creating community solidarity among urban communities who are very heterogeneous in their socio-cultural background. Sufism aesthetic values can be obtained by adherents through various religiosity activities (dhikr, praying, preaching and shalawat) and the arts of Sufism (music, songs, dances, fashion creativity).